Rancang Bangun Aplikasi Administrasi Distribusi dan Keuangan (Studi Kasus Kantor Pemasaran Sehat Tentrem Madura) - Rizky Wijaya Kusuma; Bambang Hariadi; Nunuk Wahyuningtyas (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Marketing office of Sehat Tentrem Madura is owned by Pabrik Sehat Tentrem Jaya Lestari. Marketing office of Sehat Tentrem Madura have to distributed and to marketed product of Pabrik Sehat Tentrem Jaya Lestari within Madura Island regional. Problem that show by process at marketing office of Sehat Tentrem Madura specially administration of distribution and financial is physical based data documentations which if broken then should remake the new document. Solution of the problem is to design an application of administration of distribution and financial which is function to maintenance data of sales, payment’s data, goods distribution’s data, and data of financial. Based on testing system, the application capable to executed the administration’s function at marketing office of Sehat Tentrem Madura. The application is capable to be developed become information system of marketing management’s with added accounting and return of goods processes.